Efektivitas Program Pelatihan Pilah Sampah Di Indonesia: Literature Review (2022-2025) - Mirma Yudha Firdausi; Rahmat Imaduddin; Yudha Prapantja; Zulfitria Zulfitria (Universitas Muhammadiyah Ponorogo, 2026)
The transformation of waste management in Indonesia requires substantial changes in public behavior, particularly in the practice of waste sorting at the source, which remains limited. This study aims to comprehensively analyze the effectiveness of various waste-sorting training models and to identify the key factors influencing their success in shaping public mindset and behavior. The research employed a Systematic Literature Review (SLR) by examining six indexed scientific articles published between 2022 and 2025 that focus on awareness-building and basic educational interventions in school and residential settings. The synthesis of findings indicates that the effectiveness of training programs does not operate in isolation but is simultaneously influenced by three main factors: (1) technical factors, including the availability of supporting infrastructure such as segregated waste bins; (2) cognitive factors related to participants’ understanding, facilitated through instructional methods, visual demonstrations, and interactive simulations; and (3) policy-related factors involving the implementation of regulations and the role of social role models. The results reveal that while waste-sorting training programs are highly effective in improving knowledge among students and community members, a gap remains in translating knowledge into consistent behavioral change. This gap highlights the need for continuous mentoring supported by adequate infrastructure to sustain behavioral consistency. Overall, the study indicates that maximum cognitive effectiveness is achieved through the integration of interactive educational methods, complemented by sufficient physical facilities and reinforced through continuous assistance or binding regulatory strategies that incorporate elements of positive enforcement to maintain long-term behavioral change.